Cointegration and Causality between non-bank financial intermediaries and economic growth in Malaysia - Islam, Mohd Aminul (2010)
The question whether financial development influences economic growth has been examined in a large number of studies over the past four decades. Theoretically, the positive effects of financial development on economic growth are credited primarily to the functions it plays in the mobilization and allocation of resources needed to undertake productive investment activities by various economic agents. Theoretical literature argued that the increased availability of financial instruments and institutions greatly reduces transaction and information costs in economy which in turn influences savings rate, investment decisions, undertaking of technological innovations and hence the economic growth. A great deal of empirical works has also tested the finance-growth hypothesis in a various settings using different indicators of financial development in cross-country or time series studies. The tests found mixed results. They are; no causal relationship, growth causes financial development, financial development causes growth, and bidirectional relationship. However majority of the findings support that financial development plays the leading role in influencing economic growth. Surprisingly; most of the existing finance-growth literature uses either bank development or stock market development as proxy for financial development ignoring the development of non-bank financial intermediaries (NBFIs) as one of the significant components of the financial system development and its relationship with economic growth. In this paper we made an attempt to fill in the gap by investigating the causal relationship between NBFIs and economic growth in Malaysia for the period 1974-2004. By employing ARDL bounds testing approach to cointegration and the Granger non causality test in a multivariate vector error correction mechanism (VECM), we found that nonbank financial intermediaries and economic growth are cointegrated when economic growth is treated as the dependent variable. The finding shows evidence of a long-run causality running from nonbank financial intermediaries to economic growth, but not the vice versa.